Midgut volvulus in newborns: initial symptoms and clinical course - Shiohata, Takeshi; Sotodate, Genichiro; Takashimizu, Nao; Toya, Yukiko; Wada, Yasunori; Matsumoto, Atsushi; Konishi, Yu; Ito, Ai; Oyama, Kotaro (Journal of Iwate Medical Assiociation, 2019)
Following treatment of a newborn with midgut volvulus presenting with nonspecific symptoms resulting in delayed diagnosis and poor outcome, we aimed to investigate all cases of midgut volvulus in newborns admitted to our neonatal intensive care unit in the past 10 years. Initial symptoms and clinical course were documented in order to elucidate critical signs for early diagnosis.Four newborns were included. One exhibited poor feeding, fretfulness, lethargy, and abdominal distention without bilious vomiting on day 20 after birth. Despite the absence of an accurate diagnosis by abdominal ultrasonography, emergency surgery was performed 20 hours after presentation. Widespread bowel necrosis had occurred and the patient eventually died as a result.The remaining three newborns developed bilious vomiting without abdominal distension 0-1 days after birth. In all three cases, midgut volvulus was diagnosed by the whirlpool sign on abdominal ultrasonography, and surgical repair resulted in a good outcome.Typical cases of neonatal midgut volvulus present with bilious vomiting within the first week of life; ultrasonographic finding of the whirlpool sign supports the diagnosis.Although poor feeding, fretfulness, and lethargy without bilious vomiting are atypical of neonatal midgut volvulus, this diagnosis should always be considered in cases presenting these symptoms in the neonatal period.